Analisis perubahan densitas dan viskositas minyak goreng bekas sebelum dan sesudah proses transesterifikasi secara termodinamika - Ningrum, Resti Ayu; Salawali, Rismul Trianto; Silvany, Rika; Rizky, Putri (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2026)
Used cooking oil is a household waste that poses a significant environmental hazard if not properly managed. One promising approach to its utilization is transesterification, which converts the oil into biodiesel with physical properties that are more suitable for fuel applications. This study aimed to investigate the thermodynamic changes in the density and viscosity of used cooking oil before and after the transesterification process under different pH conditions and to determine the most efficient reaction condition based on the Gibbs free energy of activation (ΔG‡). A laboratory experimental design was employed using used cooking oil as the raw material. The oil was subjected to transesterification at five different pH levels (6, 7, 8, 9, and 10). The research samples consisted of untreated used cooking oil and the methyl ester products obtained after transesterification under each pH condition. A convenience sampling technique was applied. Density was measured using a pycnometer, whereas viscosity was determined using a viscometer. Thermodynamic parameters were subsequently calculated from the experimental data. Quantitative data analysis was performed by comparing the density and viscosity values before and after transesterification and by calculating the Gibbs free energy of activation (ΔG‡) for each pH condition. The results demonstrated that the density of used cooking oil decreased from 0.908 g/cm³ to 0.870–0.872 g/cm³, corresponding to a reduction of 0.028–0.042 g/cm³. Similarly, viscosity decreased markedly from 27 cP to 4.1–6.2 cP, representing a reduction of 20.8–22.9 cP. Thermodynamic analysis revealed that the Gibbs free energy of activation (ΔG‡) ranged from 99.84 to 102.17 kJ mol-1. The reductions in density and viscosity indicate that the transesterification process successfully converted used cooking oil into methyl esters (biodiesel) with physicochemical properties that more closely comply with fuel quality standards. Furthermore, pH significantly influenced the reaction rate and system stability during transesterification. Among the investigated conditions, pH 9 yielded the lowest Gibbs free energy of activation (99.84 kJ mol-1), indicating the most thermodynamically favorable and efficient reaction condition.